Systemic Controls for Activating Artificial Intelligence Technologies in the Enforcement System and its Procedures: An Analytical Study - Ahlam Saad Abdullah Al-Zahrani; Al-Hanouf Abdulaziz Al-Sulami (International Journal of Law Research and Studies, 2026)
This study investigates the regulatory frameworks governing the integration of Artificial Intelligence (AI) and Blockchain within the Saudi enforcement system, with a specific focus on the legal conceptualization of the "Smart Enforcement Deed." The research problem addresses the existing legislative gap regarding algorithmic liability and the challenge of reconciling procedural automation efficiency with the preservation of the debtor’s legal and Sharia safeguards. Utilizing a comparative analytical methodology, the study concludes that while predictive AI significantly reduces enforcement timelines and enhances asset-tracking precision, the "algorithmic opacity" remains a major hurdle to judicial transparency. The study recommends the development of a specialized "Judicial AI Governance Framework" that strictly demarcates automatable procedural tasks from discretionary judicial functions—which must remain under human jurisdiction. Furthermore, it proposes the establishment of a technical oversight body to ensure the neutrality of smart systems and their alignment with Sharia objectives and Saudi Vision 2030.